Co‐Culture of Keratinocyte‐Staphylococcus aureus on Cu‐Ag‐Zn/CuO and Cu‐Ag‐W Nanoparticle Loaded Bacterial Cellulose:PMMA Bandages. Issue 1 (28th November 2018) - Altun, Esra; Aydogdu, Mehmet Onur; Crabbe‐Mann, Maryam; Ahmed, Jubair; Brako, Francis; Karademir, Betul; Aksu, Burak; Sennaroglu, Muge; Eroglu, Mehmet S.; Ren, Guogang; Gunduz, Oguzhan; Edirisinghe, Mohan
Abstract: Pressurized gyration and its sister processes are novel methods to produce polymeric fibers. Potential applications for such fibers include wound dressings, tissue engineering scaffolds, and filters. This study reports on a pressurized gyration technique that employs pressured N2 gas to prepare biocompatible wound dressing bandages from bacterial cellulose and poly (methylmethacrylate) polymer blended with alloyed antimicrobial nanoparticles. Resulting bandages are manufactured with high product yield and characterized for their chemical, physical, and mechanical properties. Increased density in solutions with additional antimicrobial nanoparticles results in increased fiber diameters. Also, addition of antimicrobial nanoparticles enhances ultimate tensile strength and Young's modulus of the bandages. Typical molecular bonding in the bandages is confirmed by Fourier‐transform infrared spectroscopy, with peaks that have higher intensity and narrowing points being caused by additional antimicrobial nanoparticles. More so, the cellular response to the bandages and the accompanying antimicrobial activity are studied in detail by in vitro co‐culture of Staphylococcus aureus and keratinocytes. Antimicrobial nanoparticle‐loaded bandage samples show increased cell viability and bacteria inhibition during co‐culture and are found to have a promising future as epidermal wound dressing materials. Abstract : Bacterial cellulose‐polymer‐antimicrobial nanoparticle blends are processed using pressurized gyration to manufacture wound dressing bandages which are characterized by measuring product yield, fiber morphology, structure and many key bandage‐properties. In vitro co‐culture tests are performed to investigate biocompatibility and accompanying antimicrobial activity using Staphylococcus aureus and keratinocytes. Some bandages show significant higher cell viability and bacteria inhibition.